Troubleshooting electrical/electronic systems workbook - Mazur, Glen (American Technical Publishers, 2002)
This Workbook is activity oriented, with 26 Tech-Cheks and 26 Trade Tests corresponding to the 26 chapters in Troubleshooting Electrical/Electronic Systems. It contains 136 Worksheets based on eight sets of electrical/electronic prints.